Therapeutic potential for KCC2-targeted neurological diseases - Kazuo Tomita; Yoshikazu Kuwahara; Kento Igarashi; Junichi Kitanaka; Nobue Kitanaka; Yuko Takashi; Koh-ichi Tanaka; Mehryar Habibi Roudkenar; Amaneh Mohammadi Roushandeh; Akihiro Kurimasa; Yoshihiro Nishitani; Tomoaki Sato (Elsevier, 2023)
Patients with neurological diseases, such as schizophrenia, tend to show low K+-Cl- co-transporter 2 (KCC2) levels in the brain. The cause of these diseases has been associated with stress and neuroinflammation. However, since the pathogenesis of these diseases is not yet fully investigated, drug therapy is still limited to symptomatic therapy. Targeting KCC2, which is mainly expressed in the brain, seems to be an appropriate approach in the treatment of these diseases. In this review, we aimed to discuss about stress and inflammation, KCC2 and Gamma-aminobutyric acid (GABA) function, diseases which decrease the KCC2 levels in the brain, factors that regulate KCC2 activity, and the possibility to overcome neuronal dysfunction targeting KCC2. We also aimed to discuss the relationships between neurological diseases and LPS caused by Porphyromonas gingivalis (P. g), which is a type of oral bacterium. Clinical trials on oxytocin, sirtuin 1 (SIRT1) activator, and transient receptor potential cation channel subfamily V Member 1 activator have been conducted to develop effective treatment methods. We believe that KCC2 modulators that regulate mitochondria, such as oxytocin, glycogen synthase kinase 3β (GSK3β), and SIRT1, can be potential targets for neurological diseases.